Relatório de Estágio Profissional "O caminho da descoberta da docência por uma professora-estagiária". - Tanya Costa Poças (2017)
In the last year of the Master's Degree in Teaching Physical Education in Basic and Secondary Education of the Faculty of Sport of the University of Porto, it is the responsibility of the pre-service teacher to complete a year of practicum, characterized by all the learning carried out in the previous year. It is where the pre-service teacher applies the acquired knowledge, theoretical and practical, in a real context, in which the pre-service teacher adopts the role of the main actor of practice. This practice is carried out in a cooperating school, where a teacher of the school and another one from the faculty guide the preservice teacher. This report aims to reproduce all the work done during this year and to portray, in detail, all the experiences I have achieved. This practicum report is constituted by an initial chapter "Introduction", where the contextualization of this document is expressed; The "Personal Framing" chapter, which expresses my life, academic and sports-wise, and where I reflect on the reasons that led me to the path of the teaching profession; The chapter on "Institutional Framework", sets out the context of the school where I completed my practicum, Almeida Garrett High School, the practicum group in which I was enrolled, the cooperating teacher, the supervisor teacher and my two classes; The chapter of the "Operational Framework", which describes all the work carried out throughout the year, is divided into three main areas of intervention: Area 1 - Teaching-Learning Organization and Management; Area 2 - Participation in School And Relations with the Community and Area 3 - related to Professional Development, corresponding to the research study. The last chapter concerns the main conclusions and future perspectives.